Pengaruh Ummah dan Integrasi Sosial Politik dalam Konstruksi Ketatanegaraan Islam Demokratis di Indonesia - Faza ‘Ainun Najah; Enggar Wijayanto (CV. Creative Tugu Pena, 2024)
The concept of ummah in the Medina charter is one of the fundamental principles that forms the basis of state life. Historically, the establishment of the Medina charter was a historic moment, how the beginning of the development of Islam into a country with a government system that prioritized democratic principles. The existence of obstacles to the propagation of Islam in the Mecca region encouraged the Prophet Muhammad SAW to emigrate to Medina. These obstacles have given rise to symptoms of socio-political instability, where an agreement for coexistence cannot be reached. Therefore, this article will describe the concept of the ummah in the Medina charter as socio-political integration and how it is actualized in Indonesia. The research method used uses a library research model, with secondary data sources. The results of the research show that the Ummah Principles in the Medina Charter show a progressive and revolutionary step, namely an agreement that is able to reconcile various conflicting entities, to make peace with each other and work together to build a better social and political order based on an agreement known as charter of Medina. A modern country like Indonesia currently uses the constitution as the basis for national and state life which is the source of the regulations that exist under it. Democratic values ​​where people's involvement in state life is always prioritized and put forward to safeguard rights regardless of social status.